KAJIAN KINETIKA ADSORPSI LOGAM TIMBAL (Pb) OLEH ADSORBEN PASIR TERAKTIVASI NAOH DENGAN VARIASI KONSENTRASI - Karbeka, Martasiana (Lantanida Journal, 2024)
In this research, a study of the adsorption kinetics of heavy metal Pb(II) with white sand adsorbent has been carried out. The use of white sand as an adsorbent is based on the habits of the people who use white sand to purify water. For wider use, in this study, it was used to adsorb lead metal which has a high toxicity. Increased the adsorption power of white sand, chemical activation was carried out using NaOH with various concentrations of 2, 4 and 6 M. Adsorption kinetics of Pb(II) by adsorbents were carried out using a batch system with time variations of 15, 30, 60, 90, 120 minutes. The behavior pattern of Pb(II) absorption by the adsorbent was studied using first-order, second-order kinetic models, pseudo-first-order Lagergren's equation and pseudo-second-order Ho's equation. The results showed that the absorption of Pb(II) by sand adsorbents in various variations, both control and activated NaOH 2, 4 and 6 M, followed a pseudo-second-order adsorption kinetics with a coefficient of determination (R2) of 1. In addition, based on kinetic studies pseudo second order there is no value comparison between qe, exp and qe, hit. The highest k value was found in the 4 M NaOH activated sand adsorbent, which was 206.921 g/mg.h, indicating a faster absorption rate of the adsorbate by the adsorbent. Thus, the activation of the adsorbent at variations in base concentration affects the surface area of the adsorbent where the greater the surface area, the faster the absorption rate of Pb(II).